Asuhan Kebidanan Continuity of Care pada Ny. K dengan Penerapan Aromaterapi Lavender dan Kompres Aloevera - Okta Saprina; Hikmah Ifayanti; Nila Qurniasih (Jurnal Ventilator, 2024)
This research is a comprehensive midwifery care case study on Mrs. K from pregnancy to postpartum family planning conducted at the PMB Okta Saprina, S.Tr.Keb and Mrs. K's home from October-December 2023. The assessment during pregnancy found complaints of frequent urination which were addressed by counseling on reducing drinking at night. During labor, Mrs. K experienced severe pain on a scale of 8, which was reduced to moderate pain on a scale of 5 after being given lavender aromatherapy. Labor care stages I-IV were normal according to theory and without complications. The baby was born spontaneously, full-term, without complications. During the postpartum period, Mrs. K experienced breast engorgement which was treated with aloe vera compresses for 7 days until the complaint was resolved. Care for the newborn and postpartum period was according to standards. At 42 days postpartum, Mrs. K chose to use 3-month injectable contraception after being screened with the KLOP wheel. The management provided to Mrs. K was in accordance with evidence-based practice in providing comprehensive midwifery care, namely counseling for frequent urination, lavender aromatherapy for labor pain, and aloe vera compresses for breast engorgement with satisfactory results.